Письма Анастасии Манцевич к Марии Вязьмитиной - Бузько, А.В. (Археологія і давня історія України, 2019)
В статье публикуются фрагменты 43 писем от Анастасии Манцевич к Марии Вязьмитиной за тридцатилетний период плодотворной научной работы двух ученых (1952—1982 гг.). The paper gives the review of epistolary materials for the biography of two archaeologists — Dr. Anastasia Mantsevych from Leningrad (1899—1982) and Dr. Maria Viazmitina from Kyiv (1896—1994). The documents are retained in Maria Viazmitina’s personal fund (N 34) in the Scientific Archive of the Institute of Archaeology of NASU.